HUBUNGAN FREKUENSI KUNJUNGAN ANTENATAL CARE DAN DUKUNGAN SUAMI DALAM MENGKONSUMSI TABLET FE DENGAN ANEMIA IBU HAMIL - Rokhamah, Rokhamah (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2019)
Anemia in pregnant women is a condition where a pregnant woman experiences an iron deficiency in her blood. WHO determined the incidence of pregnant anemia ranged from 20% to 89% by determining Hb> 11 g% as a basis.The purpose of the study was to determine the relationship between the frequency of ANC visits and husband's support in consuming Fe tablets with the risk of anemia in second trimester pregnant women in the work area of the Singosari health center. This study was designed with analytical methods and cross sectional approaches. The sample of this study were 30 trimester II pregnant women.The results of data analysis showed that the variable X1 (Frequency of Visit ANC) had a significant relationship with the variable Y (Risk of Anemia) with t-count > t-table which was 4.539 > 2.048, and variable X2 (Husband Support) had a significant relationship with variable Y (Risk of Occurrence Anemia) with a t-count > t-table that is 2.929 > 2.048. The value of F-count > F-table which is 11.302> 3.35 means that there is a significant influence between the Frequency of ANC Visits and Husband's Support with the Risk of Anemia. R-square value of 0.456% means that both variables X significantly influence the Y variable by 45.6%, while the other 54.4% is influenced by other factors not examined. From the two variables X, it is known that the more dominant variable Y is X1 (Frequency of ANC Visits) with a value of t-count> t-table, which is 4.539 > 2.048.There are the influence of ANC Frequency Visit Variable (X1) and Husband Support in Consuming Fe (X2) Tablets with the Risk of Anemia (Y). Respondents should always make ANC visits and routinely take Fe tablets so that the risk of anemia can be prevented early.